AN ERROR ANALYSIS OF SIMPLE PAST TENSE IN THE NARRATIVE WRITING PRODUCED BY GRADE NINE JUNIOR HIGH SCHOOL - budianto, suhartawan (Faculty of Letters, Dr. Soetomo University, 2019)
The objective of this study was to find the types of errors made by the grade nine junior high school in using Simple Past Tense in writing narrative. The classification of errors in this study is divided into four categories; they are omission, addition, misformation, and misordering. The subject of this study consists of 17 students of nine grade of SMPN 2 Sidoarjo who have more than 100 words writing. The method used in this study was descriptive analysis method to describe students? errors and analyze the data by using formula: = × %, P=Percentage, F=Frequency of errors made, N=Total of students? errors. The data was taken from the test; it was written test. The findings showed that there are 63 errors made by the students in the first test. The most frequent errors made by the students in their narrative writing focused on the use of simple past tense is misformation which consists of 33 errors or 52%, omission with 15 of total errors or 24 %, addition with 12 of total errors or 19 % and misordering 3 of total errors or 5%. The second test showed that there are 9 errors made by the students in the second test. The most frequent error made in second test by the nine grade students of SMPN 2 Sidoarjo is omission with 5 of total errors or 45 %. The second is Misformation with 4 of total errors or 36 %. The next is Addition with 2 of total errors or 19 %. The last is Misordering 0 of total errors or 0 %.